Strain Sensor with Enhanced Sensitivity for Wearable Electronics Using an Over‐Balanced Planar Elastomer. Issue 2 (7th October 2021) - Nie, Meng; Wen, Lei; Chen, Shuning; Ai, Lu; Shen, Jingcheng; Zhao, Yu‐na; Yin, Kuibo; Dou, Guangbin
Abstract: Flexible sensor technologies have gained extensive interest in recent years owing to the increasing demands of wearable electronics. Here, the authors propose a flexible strain sensor with enhanced sensitivity by designing a new sensing approach for strain detection. The sensing approach uses an over‐balanced planar elastomer (OBPE) inspired by Kirigami‐like auxetic structure for stretchable sensing. The OBPE substrate is designed and fabricated with four polydimethylsiloxane (PDMS) supporting beam embedded into Ecoflex elastomer to realize auxetic characteristics. The auxetic characteristics induce the sensing region of the sensor to expand in directions both along and orthogonally to the stretch loading. Consequently, the local disconnections of the electrically linked paths composed of multi‐wall carbon nanotubes (MWCNTs) in the sensing region are enhanced. Gauge factor of the OBPE strain sensor is improved up to 6 times higher than the typical strain sensor without OBPE architecture. Therefore, the enhanced sensor outputs the stronger electrical signals than the typical sensor in perceiving human motions. Moreover, the two‐step casting fabrication is a low‐cost process and suitable for large volume manufacturing. In addition, as this sensing method is independent of the constituent conductive materials, it has the potential to be further employed for developing other stretchable strain sensors. Abstract : The authors propose a flexible strain sensor with enhanced sensitivity by designing a new sensing approach for strain detection. The sensing approach uses an over‐balanced planar elastomer (OBPE) inspired by auxetic structure for stretchable sensing. Gauge factor of the OBPE strain sensor is improved up to 6 times higher than the typical strain sensor without OBPE architecture.